Photovoltaic Cell Fed 3-Phase Induction Motor Using MPPT Technique - Gudimetla Ramesh; Kari Vasavi; S.Lakshmi Sirisha (Institute of Advanced Engineering and Science, 2014)
This Paper emphasizes on proposing a cost effective photovoltaic (PV) fed 3 phase Induction motor drive which serves for rural pumping applications. Generally in a standalone system, the PV unit will charge the battery and the battery set up in turn will serve as a source for the inverter. A new single stage battery less power conversion is employed by designing a maximum power point tracker (MPPT) embedded boost converter which makes the overall cost of the setup to go down considerably. The realized as a prototype consisting PV array of 500watts, MPPT aided boost converter, three phase inverter and a three phase squirrel cage induction drive of 300 watts. An efficient and low cost micro controller dspic4011 is used a platform to code and implement the prominent perturb and observe MPPT technique .Sinusoidal pulse width modulation (SPWM) is the control technique employed for the three phase inverter. To validate the experimental results simulation of the whole set up is carried out in matlab /simulink environment. Simulation and hardware results reveal that the system is versatile.DOI: http://dx.doi.org/10.11591/ijpeds.v5i2.6209